Diversity of foliar fungi in the forest flora of North-eastern U.P.: Five new species of Corynespora Gussow - and NASIM AHMAD, VIVEK KUMAR PAL*, MASOOD AKHTAR, D.K. AGARWAL, R.K. CHAUDHARY (Indian Phytopathology, 2007)
This paper deals with descriptions of five novel taxa of genus Corynespora viz., C. baliospermigena sp. nov., C. clerodendri-viscosi sp. nov., C. nanospora sp. nov., C. sapptacearum sp. novo and C. xylosmaelongifoliae sp. novo occurring on Baliospermum montanum (Willd.) Mull-Arg. (Euphorbiaceae), Clerodendrum viscosum (Linn) Ktze. (Verbenaceae), Premna mucronata (C.B. Clarke) Roxb. (Verbenceae), Madhuca indica Gmel. (Sapotaceae) and Xylosma longifolia Clos. (Flacourtiaceae) respectively.